Seorang Laki-laki Usia 16 Tahun yang Mengalami Drowning dan Pneumotoraks Paska Pemasangan Ventilator Mekanik: [Pneumothorax in a Ventilated Young Man after Drowning: A Case Report] - Ira Nurrasyidah; Winariani Koesoemoprodjo (Jurnal Respirasi, 2015)
Background; Drowning is defined as respiratory impairment due to submersion/immersion in liquid. The liquid/air interface at the entrance of the airway prevents the victim from breathing air. According to the World Health Organization (WHO), 0.7% of all deaths worldwide - or more than 500,000 deaths each year - are due to unintentional drowning. Drowning is the second leading cause of unnatural death after road traffic injuries. Most of these deaths occur in countries with low or middle per capita income. Case; A16-years-old man rescued after drowning in the mud puddle for 15 minutes. He was unconscious, cyanosis, dyspnea and cough with blood and mud. After receiving oxygen in the nearest hospital he got conscious but still dyspnea. He came to our hospital and after undergone several examination we concluded that he had lung edema, ARDS and pneumonia aspiration. Patient immediately intubated and got mechanical ventilation. Five days later patient encounter pneumothorax on the right hemithorax, maybe due to barotrauma and we perfomed a chet tube insertion for three days. Patient had a good progression, there was no deficit neurologic and injury in the other organ. On follow up five months after patient hospitalized revealed normal condition on chest x ray.